Membangun Teori Politik Hukum Islam di Indonesia - Abdul Halim (Universitas Islam Negeri Jakarta, 2013)
Abstract: Constructing a Political Theory af Islamic Law in Indonesia. This study confirms that the transformation of Islamic law into national law has no correlation with the struggle towards an Islamic country or Islam as the foundation of the state. Islamic law legislation are regulations that have a positive contribution to strengthening the commitment of Muslims towards the Indonesian nation-state. This study refutes the notion that the accommodation of Islamic law within legislation is an agenda aiming towards an Islamic state. The process of accommodation of Islamic law does not need to be feared, because the process is supported by the power of cultural Islam. Besides, Islamic law is at the legal source level so that the accommodation into pre-legislation undergoesstringent testing in order to always be in accordance with Pancasila and the 1945 Constitution.Keywords: politic law, legislation, Islamic law, constitutional theory and the theory of accommodationAbstrak: Membangun Teori Politik Hukum Islam di Indonesia. Studi ini menegaskan bahwa transformasi hukum Islam ke dalam hukum nasional tidak memiliki hubungan dengan perjuangan menuju negara Islam atau Islam sebagai dasar negara. Legislasi hukum Islam menjadi perundang-undangan memiliki kontribusi positif dalam memperkuat komitmen umat Islam terhadap negara kebangsaan Indonesia. Studi ini membantah pendapat yang menyatakan bahwa akomodasi hukum Islam oleh peraturan perundang-undangan merupakan agenda menuju negara Islam. Proses akomodasi hukum Islam tidak perlu dikhawatirkan karena proses itu didorong oleh kekuatan Islam kultural. Selain itu, hukum Islam berada pada tataran sumber hukum sehingga akomodasinya ke dalam perundang-undangan terlebih dahulu mengalami pengujian yang ketat agar selalu sesuai dengan Pancasila dan UUD 1945.Kata Kunci: politik hukum, legislasi, hukum islam, teori konstitusi dan teori akomodasiDOI: 10.15408/ajis.v13i2.938